New perspectives on fertility in transwomen with regard to spermatogonial stem cells - Jennifer Dabel; Florian Schneider; Joachim Wistuba; Sabine Kliesch; Stefan Schlatt; Nina Neuhaus (Bioscientifica, 2023)
Objective: Germ cells of transwomen are affected by gender-affirming hormone therapy (GAHT). Fertility will be lost after surgical intervention; thereby, fertility preservation becomes an increasingly imortant topic. This study investigated if the absolute number of spermatogonia in transwomen is comparable at the time of gender-affirming surgery (GAS) to that in pre-pubertal boys. Methods: We carried out a retrospective study of testicular tissues from 25 selected subjects, which had undergone a comparable sex hormone therapy regimen using cyproterone acetate (10 or 12.5 mg) and estrogens. As controls, testicular biopsies of five cisgender adult men (aged 35-48 years) and five pre-/pubertal boys (5-14 years) were included. Testicular tissues were immunohistochemically stained for MAGE A4-positive cells, the most advanced germ cell type. The number of spermatogonia per area was assessed. Clinical values and serum hormone values for FSH, LH, testosterone, free testosterone, estradiol and prolactin were determined on the day of GAS for correlation analyses. Results: Round spermatids were the most advanced germ cell type in 3 subjects, 5 had an arrest at spermatocyte stage, while 17 showed a spermatogonial arrest. On average, testicular tissues of transwomen contained 25.15 spermatogonia/ mm3, a number that was significantly reduced compared to the two control groups (P < 0.01, adult 80.65 spermatogonia/ mm3 and pre-/pubertal boys 78.55 spermatogonia/mm3). Linear regression analysis revealed that testes with higher weight and high LH contained more spermatogonia. Conclusion: Irrespective of treatment dose or duration, spermatogenesis was impaired. Spermatogonial numbers were significantly reduced in transwomen compared to the control groups.